Innovators, imitators, and the evolving architecture of social networks - Myong-Hun Chang; Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2005)
Scientific progress is driven by innovation ?which serves to produce a diversity of ideas ?and imitation through a social network ?which serves to diffuse these ideas. In this paper, we develop an agent-based computational model of this process, in which the agents in the population are heterogeneous in their abilities to innovate and imitate. The model incorporates three primary forces ?the discovery of new ideas by those with superior abilities to innovate, the observation and adoption of these ideas by those with superior abilities to communicate and imitate, and the endogenous development of social networks among heterogeneous agents. The objective is to explore the evolving architecture of social networks and the critical roles that the innovators and imitators play in the process. A central finding is that the emergent social network takes a chainstructure with the innovators as the main source of ideas and the imitators as the connectors between the innovators and the masses. The impact of agent heterogeneity and environmental volatility on the network architecture is also characterized.
Keywords: 330; Innovator; Imitator; Connector; Social Networks; Network Architecture; Agent-Based Model; Innovation; Imitationswettbewerb; Theorie; Soziales Netzwerk